Diagnostic Findings of Sclerosing Mesenteritis and the Disease Correlations with Caecal Adenocarcinoma - Rabbinu Rangga Pribadi; Murdani Abdullah; Rizka Puteri Iskandar; Velma Herwanto; Okto Dewantoro; I Wayan Murna Yonathan; Arman Adel Abdullah; Ening Krisnuhoni; Diah Rini Handjari (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2017)
Sclerosing mesenteritis (SM) is a rare disease with non-specific clinical manifestations and should be supported by radiological examination and confirmed by histopathological evaluation. Its relationship with cancer especially caecal adenocarcinoma is still unclear. This case report describes a young man who was diagnosed as having SM and poorly-differentiated caecal adenocarcinoma.